Verruca plana on a tattoo: A case report. Issue 15 (April 2020) - Chen, Yan Jing; Nabi, Owais; Diao, Ping; Wan, Ruo Yu; LI, Li
Abstract: Rationale: Tattooing is a procedure where ink is inserted typically in the intraepidermal space of the skin. Multiple incidences of viral infections following tattooing which lead to warts have been reported in recent years. The aim of this report was to show a relatively rare adverse effect after tattooing – verruca plana. Patient concerns: A 27-year-old female presented to our department with complains of multiple verrucous papules over her 2-year-old tattoo without itch. Diagnoses: Pathological investigation confirmed the diagnosis as verruca plana. Interventions: The patient was treated with 3 cycles of liquid nitrogen cryotherapy and 5% imiquimod cream for 5 months. Outcomes: A significant improvement in her lesions was observed after the combined treatment. Lessons: Clinically, verruca plana post-tattooing is relatively less reported. We need to combine clinical manifestations with pathological results to arrive at a definitive diagnosis. Besides, there are a large numbers of post-tattoo complications and various routes of virus inoculation. Therefore, it is important for medical professionals to caution people before considering to have a tattoo.